Effect of tungsten particles on microstructure and properties of 316 L stainless steel manufactured by selective laser melting. (August 2021) - Yin, Xiaotian; Zhai, Qiang; Zhang, Qingxia; Wang, Kunlun; Meng, Lingtao; Ma, Zhenghang; Chen, Guoxia; Wang, Shenghai; Wang, Li
Abstract: Low surface hardness, low strength and poor corrosion resistance limit the further application of 316 L stainless steel (SS). Due to faster cooling rate and smaller pool, the properties of parts fabricated by selective laser melting (SLM) are often superior to traditional casting, powder metallurgy and directed energy deposition (DED) processes. In addition, due to its high hardness, strength and corrosion resistance, tungsten (W) was originally used for preparation of 316 L SS reinforced composites by SLM in this paper. Their mechanical and corrosion properties have been significantly enhanced. Different from ceramic particles of other compounds, some W particles can dissolve into the matrix well, so it can effectively inhibit the early crack caused by poor combination, thus protecting its elongation. In comparison with the pure 316 L SS samples, the yield strength (YS) of the 10 wt% W/316 L SS composites increased above 50% (from 627 MPa to 980 MPa). Interestingly, it still has an outstanding elongation rate of 19%, which is difficult for other types of reinforcing particles to achieve. At the same time, its hardness increased by 32% (from 222.7 HV to 294.3 HV). And 3 wt% W/316 L SS composites have better corrosion resistance and higher strength while maintaining original elongation. The improvement of mechanical properties is attributed to the addition of W particles, which led to grain refinement and grain boundary strengthening. The reasons for changes in corrosion resistance were also analyzed through the microstructure. Results of our study show that single element particles have application potential to metal matrix composites (MMCs) fabricated by SLM.